Echoes and misalignments: A cuir ecology through dissident temporalities and insurgent writing - Matías Gutiérrez, Leonel (2026)
This essay examines the possibility of a cuir ecology rooted in Latin America from a dissident, situated, and critical perspective. Grounded in a non-binary positionality, it articulates queer temporalities, affective archives, and insurgent writing as practices that challenge historical linearity, the nature/culture divide, and normative modes of inhabiting the world. Engaging with recent debates in Latin American cuir thought, it analyzes forms of resistance that emerge through sensibility, insurrectional care, and the persistence of fragmented memories. The poetic series Varones en obra is incorporated as a situated artistic practice in which the urban landscape functions as an affective archive, and bonds between men unfold as territories of desire and tension. The analysis advances an understanding of cuir ecology as an open, relational, and continually shifting practice sustained by disruption, vulnerability, and fragmentation as valid modes of knowledge, enabling alternative forms of coexistence, affectivity, and care beyond the normative and extractivist frameworks that shape dominant environmental discourses.